PENGARUH MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MENGENAL EMOSI ANAK USIA 3-4 TAHUN - Widya Khoirun Nisa’; Muhammad Reza; Dewi Komalasari; Wulan Patria Saroinsong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze improving the ability of 3-4 year old children to recognize emotions. The background of this research is based on the low and underdeveloped ability to recognize emotions in early childhood, which is often caused by limited media and opportunities for direct exploration of emotional recognition thru Flash Cards. The main difference between the Flash Cards for emotional recognition in this study and other Flash Cards lies in the focus of the material and the depth of emotional stimulation. These Flash Cards are specifically designed to develop children's ability to recognize emotions, displaying illustrations of facial expressions and body language that are easily recognizable by young children. The presentation of positive and negative emotional variations helps children understand the diversity of emotions as part of everyday experience. This study uses a quantitative approach with a Quasi-Experimental design of the Nonequivalent Control Group type, involving an experimental group and a control group, each consisting of 20 children. Data was collected thru observation and documentation and analyzed using the Mann-Whitney U Test manually and with the help of SPSS version 26. The research results show that the experimental group receiving treatment thru emotion recognition activities using Flash Cards experienced a more significant improvement compared to the control group in terms of content, process, and context of emotion recognition. The Mann Whitney U Test, conducted manually, showed a significance value, with the smallest U value obtained being U₁ = 1.5. Therefore, the U table value was 13, leading to the conclusion that there was a significant difference between the experimental and control groups. The rejection of H₀ indicates that the treatment given to the experimental group influenced the improvement in students' learning outcomes compared to the control group. The average posttest score for the experimental group was 54.69%, which was higher than the control group's average score of 25.62%. This finding indicates that the Flash Card media for recognizing emotions significantly improved the ability of 3-4 year old children to recognize emotions. Therefore, Flash Card media can be considered an effective learning model for stimulating the development of emotional recognition in early childhood.